Baloch Ethnic Nationalism: A Threat to National Integration of Pakistan - Majeed, Gulshan (Annals of Human and Social Sciences, 2024)
The objective of this paper is to highlight actual grievances of Baloch ethnicity and responses by authorities. This paper has explained about nationalistic tendencies among Baloch people. Pakistan’s society is plural with different religious, linguistic and regional identities. One of the serious challenges that Pakistan has been facing since 1947, is the self-assertion of various ethnic identities in a hostile way which has been posing a threat to the integrity of state. Baloch nationalism has been posing a major threat to the national integration of Pakistan through various insurgent movements on different occasions of history of Pakistan. Researcher had used descriptive analytical research method to conduct this research and secondary sources have been used to collect data. Researcher did highlight consequences if needs of Baloch people are not being met by the political system. Sense of belongingness towards system should be created among Baloch to enhance national integration In Pakistan.